Utilization of civet coffee (Coffee arabica var. catimor) rejects in combination with malunngay (Morringa oleifera) for the production of civet-moringa coffee concoction Sheena Justy Marie C. Domingo. - Domingo, Sheena Justy Marie C. (2010)
A study on the utilization of civet coffee peaberry in combination with malunggay for the production off civet-moringa concoction was conducted. Three formulations of moringa-2.35%, 5% and 7.35%, were tried and evaluated by 20 panelists. Using Friedman's test no significant difference among three formulations was identified. Formulation with 7.35% moringa was used for the production of the final product which was added with three different amount of sugar--5.25g.,and 10.5g and 15.75g, for every 250 ml of the concoction. Using gain Friedman"s test , no significant difference among the three amount of sugar was identified hence smallest amount was used for the sensory evaluation of the final product., 9-Hedonic scale rating was used by 60 panelist and using frequency distribution and percentiles the obtained general acceptability of the final product was high from both black coffee and non-black coffee drinkers. MSI curve of the final product illustrates its low hyrogroscopity directing its critical moisture content which ranges from .03846 to 0.03249 g H2)/g solids at 30% to 40% RH. Through FRAP assay, the antioxidant capacity of the final product was determined. Using Mann-Whitney U test, it shows that antioxidant capacity of civet-moringa-654.58 uml Fe/L sampleis significantly different form the control (without moringa)-536.89 umol Fe/Lsample. Thereby, 250 ml brewed civet-moringa using 10 g generates antioxidants that has capacity of 536.89 umol Fe/L sample. The product is a rare functional coffee concoction, which more importantly, is nutritious and healthy.